GAMBARAN ALERGEN PASIEN RINITIS ALERGI DI POLIKLINIK THT RSUP SANGLAH DENPASAR TAHUN 2012-2013 - Sari, Putu Suwita; Dwi Saputra, Komang Andi (E-Jurnal Medika Udayana; Vol 6 No 7 (2017): E-Jurnal Medika Udayana, 2017)
Allergic rhinitis is not a deadly disease, but it can cause significant decrease in productivity and quality of patient life. Allergen investigation in allergic rhinitis patient is important to determine the specific cause of allergy, so that the patient can do avoidance in order to prevent the recurrence of the disease. The purpose of this study is to obtain the allergen profile in allergic rhinitis patient. This study is a descriptive-retrospective study using secondary data from ENT Department and Medical Record Department of Sanglah Hospital in 2012-2013. The data from patient medical record will be calculated and analyzed. From 52 samples, 34 patients shows positive skin prick test (SPT) results. About 16 patients (30.8%) are positive for both inhalant and ingested allergen, 15 patients (28.8%) only positive to inhalant allergen, and 3 patients (5.8%) only positive for ingested allegen. The most common allergen is house dust mite with  24 patients (46.2%). Crab is the second most common with 15 patients (28.8%). It can be summarized that house dust mite is the most common allergen with 46.2%. Education and precaution against the exposure of house dust mite is important to all allergic rhinitis patients   Keywords : allergic rhinitis, allergen, skin prick test